In Vitro PDGF-B Gene Silencing Studies and In Vivo Delivery of siRNA to the Rat Kidney Using Chitosan/siRNA Nanoplexes - ÖZBAŞ, SUNA (MARMARA UNIV, FAC MEDICINE, 2016)
The targeting of specific genes responsible from onset and progression of kidney diseases offer a new therapeutic strategy in the field of renal gene therapy. The altered expression of platelet derived growth factor (PDGF) is an important marker of renal diseases. In this study, we investigated in vitro gene silencing efficiency of chitosan nanoplexes containing PDGF-B and PDGFR-beta targeted siRNAs in the kidney cell lines including HEK-293 and MDCK and delivery to the kidney as an in vivo delivery system. As a result, PDGF-B expression was significantly inhibited by co-delivery of chitosan/siPDGF-B+siPDGFR-beta nanoplexes prepared using in the different weight ratios (10/1, 20/1 and 50/1). When 20/1 and 50/1 weight ratios of chitosan nanoplexes were i.v. injected to rats, chitosan/FITC-siPDGFB nanoplexes were reached to kidney tissue at 4 h after intravenous injection. These results suggest that delivery of siRNA using chitosan nanoplexes may be effective for the therapy of kidney diseases.
Keywords: siRNA; PDGF-B; PDGFR-beta; chitosan; nanoplexes; kidney; SMALL INTERFERING RNA; GROWTH-FACTOR; NANOPARTICLES; POTENTIALS; THERAPY; DISEASE; VEGF